2011
DOI: 10.1021/ef2002124
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Density: Experimental Measurements and Prediction Models

Abstract: Density is an important biodiesel parameter, with impact on fuel quality. Predicting density is of high relevance for a correct formulation of an adequate blend of raw materials that optimize the cost of biodiesel fuel production while allowing the produced fuel to meet the required quality standards. The aim of this work is to present new density data for different biodiesels and use the reported data to evaluate the predictive capability of models previously proposed to predict biodiesel or fatty acid methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
134
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 181 publications
(154 citation statements)
references
References 27 publications
12
134
0
8
Order By: Relevance
“…For the case of minority FAMEs and FAEEs the density could be predicted within a deviation of 1.5%, except for the linolenate esters at high temperatures, again due to the poor description of the polyunsaturation effect on densities. Pratas et al [36] also applied the original and the extended GCVOL models to 18 biodiesel samples of soy, rapeseed, palm, cottonseed, jatropha, and mixtures thereof at temperatures between 273.15 and 373.15 K and densities from 815 to 898 kg m À3 , and obtained overall ARDs of 0.6% and 2.7% for the original and the extended GCVOL, respectively. To solve the precision lack for the polyunsaturation ester effect, Pratas et al [36] found new parameter values A i , B i , and C i relative to the double bond (ACH@) contribution, based on density data measured for FAMEs [55,56].…”
Section: Density Prediction 431 the Group Contribution Methods (Gcmentioning
confidence: 99%
See 4 more Smart Citations
“…For the case of minority FAMEs and FAEEs the density could be predicted within a deviation of 1.5%, except for the linolenate esters at high temperatures, again due to the poor description of the polyunsaturation effect on densities. Pratas et al [36] also applied the original and the extended GCVOL models to 18 biodiesel samples of soy, rapeseed, palm, cottonseed, jatropha, and mixtures thereof at temperatures between 273.15 and 373.15 K and densities from 815 to 898 kg m À3 , and obtained overall ARDs of 0.6% and 2.7% for the original and the extended GCVOL, respectively. To solve the precision lack for the polyunsaturation ester effect, Pratas et al [36] found new parameter values A i , B i , and C i relative to the double bond (ACH@) contribution, based on density data measured for FAMEs [55,56].…”
Section: Density Prediction 431 the Group Contribution Methods (Gcmentioning
confidence: 99%
“…Pratas et al [36] also applied the original and the extended GCVOL models to 18 biodiesel samples of soy, rapeseed, palm, cottonseed, jatropha, and mixtures thereof at temperatures between 273.15 and 373.15 K and densities from 815 to 898 kg m À3 , and obtained overall ARDs of 0.6% and 2.7% for the original and the extended GCVOL, respectively. To solve the precision lack for the polyunsaturation ester effect, Pratas et al [36] found new parameter values A i , B i , and C i relative to the double bond (ACH@) contribution, based on density data measured for FAMEs [55,56]. This revised variant of GCVOL was applied to the 18 biodiesels leading to a decrease in the overall ARDs to 0.25% in density, corresponding to %2 kg m À3 [36].…”
Section: Density Prediction 431 the Group Contribution Methods (Gcmentioning
confidence: 99%
See 3 more Smart Citations